The Influence of Digital Marketing, Word of Mouth, Service Quality and Consumer Satisfaction on Purchase Decisions in Pempek Betigo Palembang Food Business in Medan - Hartono, Hartono (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of digital marketing, word of mouth, and service quality on purchase decisions through consumer satisfaction in the Pempek Betigo culinary business in Medan City. The research employed a quantitative method using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. Data were collected through questionnaires distributed to Pempek Betigo’s consumers. The results indicate that digital marketing, word of mouth, and service quality have a positive and significant impact on consumer satisfaction. Moreover, all independent variables directly and indirectly influence purchase decisions through consumer satisfaction. These findings highlight the importance of digital marketing strategies, word-of-mouth promotion, and service quality improvements in encouraging consumer purchase decisions